2005
DOI: 10.2170/jjphysiol.rp001105
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Amygdala Controls the Coital Access of Female Rats: A Possible Involvement of Emotional Responsiveness

Abstract: Partner preference and paced mating tests were accomplished in ovariectomized female rats 10 following bilateral radiofrequency lesions in the medial amygdala. Open field behavior and passive avoidance learning were also examined to investigate the underlying behavioral mechanism. Partner preference was determined in a chamber located between castrated and sexually active males. Airborne olfactory cues were presented to the female through small holes on the partition. The lesion diminished preference for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
1
26
2
Order By: Relevance
“…In general, the present data corroborate previous reports of olfactory deficits after Me lesions in female hamsters [33] and rats [34]. Male hamsters that received lesions targeted at either the anterior or posterior Me showed a reduced preference for volatiles from female-soiled over male-soiled bedding in Y-maze tests [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the present data corroborate previous reports of olfactory deficits after Me lesions in female hamsters [33] and rats [34]. Male hamsters that received lesions targeted at either the anterior or posterior Me showed a reduced preference for volatiles from female-soiled over male-soiled bedding in Y-maze tests [17].…”
Section: Discussionsupporting
confidence: 92%
“…It was concluded that such high levels of investigation toward both stimuli reflected males' inability to categorize the relevance of odor stimuli. Furthermore, it has been observed in rats that lesions of the entire Me diminished the preference for testes-intact over castrated male volatiles in females in which air was blown over a stimulus male into the female compartment [34]. In the present study, female mice that received anterior Me lesions did not spend more time investigating both odors when compared to sham females.…”
Section: Discussioncontrasting
confidence: 40%
“…This structure receives projections both from the main and accessory olfactory systems, and olfactory stimuli are crucial for the activation of approach behaviors [reviewed in [22]]. Lesion of the medial posterodorsal amygdala (MePDA) reduces these behaviors in female rats [23,24]. Furthermore, there is a substantial projection from the amygdala to the VMN [25], suggesting that olfactory stimulation reaches the VMN via the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…These salient chemosignals (often referred to as pheromones) are detected by the main (MOS) and accessory olfactory systems (AOS) and relayed to the medial amygdala (Me). The Me is critical for odor-guided courtship and reproductive behaviors in female rodents [24]. It sends axonal projections to several downstream targets including the bed nucleus of the stria terminalis (BNST), the medial preoptic area (MPA), ventromedial (VMHvm), and ventrolateral (VMHvl) divisions of the ventromedial hypothalamus, and to numerous ventral striatal targets, including the nucleus accumbens core (AcbC) and shell (AcbSh), ventral pallidum (VP), medial olfactory tubercle (mOT) and islands of Calleja (ICj) [57].…”
mentioning
confidence: 99%